Tumache Prabandh Likhaan - Oliver, Paul (SAGE Publications, 2017)
Cover – Contents – About the Author – Acknowledgements – Part 1 – Chapter 1 – Chapter 2 – Chapter 3 – Chapter 4 – Chapter 5 – Chapter 6 – Chapter 7 – Part 2 – Chapter 8 – Chapter 9 – Chapter 10 – Chapter 11 – Chapter 12 – Chapter 13 – Chapter 14 – Chapter 15 – References.
Description based on publisher supplied metadata and other sources
Keywords: Dissertations; Academic-Authorship; Electronic books